Incidence of Herpes Zoster in relationship with Climate Factors from 2009 to 2011 - Herning Adinda; Dendi Sandiono; Ihrul Prianza Prajitno (Althea Medical Journal, 2015)
Background: Herpes zoster, or shingles, is a skin or mucous infection caused by the reactivation of varicella-zoster virus (VZV). Seasonal pattern of herpes zoster incidence was reported in some countries, indicating that emergence of this disease was caused by the reactivation of latent Varicella-Zoster Virus (VZV) rather than new exposures to VZV. On the other hand, the VZV primary infection difference between tropical and temperate zones may have implications for virus reactivation as herpes zoster. The aim of this study was  to identify the incidence of herpes zoster in Dr. Hasan Sadikin General Hospital Bandung, West Java related to the change of rainfall, air temperature and humidity from 2009 to 2011.Methods: A descriptive retrospective study was carried out to 341 medical records of herpes zoster patients from Dr. Hasan Sadikin General Hospital Bandung periode 2009 to 2011. Data on climate factors, i.e. rainfall, air temperature, and relative humidity, were obtained from the Indonesian Meteorology, Climatology, and Geophysical Agency. The collected data were presented using tables and figures.Result: The highest number of herpes zoster cases occured during the period when the highest annually total rainfall and annually mean relative humidity occurred.Conclusions: The finding of this study shows that herpes zoster cases have the same pattern with the rainfall and relative humidity. These findings can inform better prevention of herpes zoster. However, further research is needed to get more comprehensive understanding on this relationship. DOI: 10.15850/amj.v2n3.591